PENGARUH LITERASI KEUANGAN SYARIAH, RELIGIUSITAS, DAN DIGITAL BANKING TERHADAP MINAT MENGGUNAKAN BANK SYARIAH DI BANK SYARIAH INDONESIA CABANG LUMAJANG: ANALISIS SEM-PLS PADA GENERASI MILENIAL - Muhammad Ichwanus Surur; Andila Ramadani (ESA, 2026)
AbstractThis study examines the influence of Islamic financial literacy, religiosity, and digital banking on millennials’ intention to use Islamic banking services. Despite the significant growth of Islamic banking in Indonesia, its market share remains below its potential, particularly among the millennial segment, which is characterized by strong technological adaptability. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 150 millennial respondents aged 25–40 years through a structured questionnaire. The measurement model assessment confirmed adequate convergent validity, discriminant validity, and reliability across all constructs. The structural model results indicate that Islamic financial literacy, religiosity, and digital banking positively and significantly influence the intention to use Islamic banks. The model explains 68.2% of the variance in behavioral intention (R² = 0.682). Among the predictors, digital banking emerged as the most dominant factor, highlighting the critical role of technological convenience, accessibility, and service efficiency in shaping millennials’ banking preferences. These findings suggest that strengthening digital transformation strategies, alongside enhancing Islamic financial literacy and value-based engagement, is essential for increasing Islamic banking adoption among younger generations.Keywords: Islamic financial literacy, religiosity, digital banking, PLS-SEM, millennials